Models to analyze public policies and national reality - Peña-Salinas, Víctor Hugo (Universidad Pedagógica y Tecnológica de Colombia, 2013)
It is essential to understand the role that public policies play in the development of a society. This work aims to analyze the context and the development of public policies, interests enclosing, their scope and effectiveness, starting from reflections based on models that have been structured for their analysis. This work also distinguishes between national and regional policies. The conclusion reached by the author is given based on the effectiveness of public policy in a country like Colombia.